Dampak Tren Tiktok Terhadap Perkembangan Moral pada Siswa - Siswi di SMA Negeri 10 Medan - Adelia Aritonang; Grace Claudia Valerina Saragih; Fanny Mustika Ayu; Kevin Cornelius Manurung; Mhiranda Sitorus; Roma Nauli Stephany Bintang; Trima Uasito Tampubolon; Jamaludin Jamaludin; Sri Yunita (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
Social media is one of the communication tools that has become an integral part of everyday life, especially for teenagers and the younger generation. This study focuses on the TikTok application. TikTok can affect children's moral character. Strong moral education is very important to protect children from the negative impacts of TikTok. This research method adopts a qualitative approach with a focus on in-depth interviews with students of SMA Negeri 10 Medan. The results of the study show that the use of TikTok among students at SMA Negeri 10 Medan has positive and negative impacts. The positive impacts include increased creativity, skills, and self-confidence, while the negative impacts include gadget addiction, the spread of age-inappropriate content, and academic disruption. Teachers' efforts to overcome these negative impacts involve education, supervision, and the use of TikTok for more positive purposes. Thus, it is important for students at SMA Negeri 10 Medan to use TikTok wisely and responsibly, and to understand the moral values ​​that are important in everyday life.